2016
DOI: 10.3847/0004-637x/828/2/71
|View full text |Cite
|
Sign up to set email alerts
|

THE Lyα–LyC CONNECTION: EVIDENCE FOR AN ENHANCED CONTRIBUTION OF UV-FAINT GALAXIES TO COSMIC REIONIZATION

Abstract: The escape of ionizing Lyman continuum (LyC) photons requires the existence of low-N H I sightlines, which also promote escape of Lyα. We use a suite of 2500 Lyα Monte-Carlo radiative transfer simulations through models of dusty, clumpy interstellar ("multiphase") media from Gronke & Dijkstra, and compare the escape fractions of Lyα ( a f esc Ly ) and LyC radiation ( f esc ion ). We find that f esc ion and a f esc Ly are correlated: galaxies with a low a f esc Ly consistently have a low f esc ion , while galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
176
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 158 publications
(196 citation statements)
references
References 119 publications
(229 reference statements)
18
176
2
Order By: Relevance
“…Galaxies with low N HI should also have high f Lyα esc (e.g., Yajima et al 2014;Dijkstra et al 2016;Verhamme et al 2017). However, aperture effects may lower f Lyα esc in the new z < 0.12 GPs compared to other GP samples (Jaskot & Oey 2014;Henry et al 2015;Izotov et al 2016b).…”
Section: Introductionmentioning
confidence: 96%
“…Galaxies with low N HI should also have high f Lyα esc (e.g., Yajima et al 2014;Dijkstra et al 2016;Verhamme et al 2017). However, aperture effects may lower f Lyα esc in the new z < 0.12 GPs compared to other GP samples (Jaskot & Oey 2014;Henry et al 2015;Izotov et al 2016b).…”
Section: Introductionmentioning
confidence: 96%
“…A shell model requires low neutral gas column density or a high outflow velocity (Verhamme et al 2015). In the case of a multi-phase model (Dijkstra et al 2016), a low-velocity offset translates to a low covering fraction of neutral gas, independent of its neutral column density and outflow velocity. In both models, however, the low-velocity offset is a consequence of the presence of low HI-column density escape routes for Lyα photons, which may also allow ionizing photons to escape (see Verhamme et al 2015Verhamme et al , 2017Dijkstra et al 2016 for more detailed discussions).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent progress has been made in the field of photo-ionization modeling (Jaskot & Oey 2013;Nakajima & Ouchi 2014;Zackrisson et al 2016;Inoue 2011), subsequently confirmed by observations (e.g., de Barros et al 2016;Vanzella et al 2016b;Verhamme et al 2016). In particular, line ratios in the rest-frame optical band like the O32 index ([Oiii]λ5007/[Oii]λ3727) and specific properties of the Lyα profile (Behrens et al 2014;Verhamme et al 2015;Dijkstra et al 2016) can provide valuable indirect probes of the physical state of the interstellar medium and of the column density of neutral gas (e.g., density-bounded or ionization-bounded), as well as the connection with the ultraviolet spectral slope, the Balmer emission lines and the Lyman continuum leakage (Zackrisson et al 2013(Zackrisson et al , 2016.…”
Section: Dynamical Mass Of Id11mentioning
confidence: 99%